2011
DOI: 10.1016/j.bbrc.2011.06.109
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a putative Crimean-Congo hemorrhagic fever virus entry factor

Abstract: Entry of enveloped viruses into cells is initiated by binding of their envelope glycoproteins (Envs) to cell surface-associated receptors. The Crimean-Congo hemorrhagic fever virus (CCHFV) has two Envs, Gn and Gc, with poorly understood role in binding to susceptible cells. We expressed codon optimized Gn and Gc, and identified independently folded soluble Env fragments, one of which (Gc residues 180-300) bound CCHFV susceptible cells supposedly by interacting with a putative receptor. This receptor binding do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 28 publications
(30 reference statements)
0
59
0
3
Order By: Relevance
“…The cellular receptor for CCHFV has not been identified, but a recent study employing the soluble ectodomains of G N and G C suggested that G C plays the major role in binding to target cells, and identified the host molecule nucleolin as essential for cell entry (Xiao et al, 2011). The virus appears to enter host cells by clathrin-dependent endocytosis (Fig.…”
Section: Replication Cyclementioning
confidence: 99%
“…The cellular receptor for CCHFV has not been identified, but a recent study employing the soluble ectodomains of G N and G C suggested that G C plays the major role in binding to target cells, and identified the host molecule nucleolin as essential for cell entry (Xiao et al, 2011). The virus appears to enter host cells by clathrin-dependent endocytosis (Fig.…”
Section: Replication Cyclementioning
confidence: 99%
“…69 Nucleolin is also believed to participate in the infection of Hepatitis C virus (HCV), herpes simplex virus (HSV) type 1, white-spot syndrome virus (WSSV) and the Crimean-Congo hemorrhagic fever virus (CCHFV). [70][71][72][73] Interestingly, nucleolin forms RNP complexes with the 3' UTR of feline calicivirus (FCV) and Norwalk virus (NV); in this regard, lowering nucleolin reduced viral protein synthesis and FCV replication, while the mobilization of nucleolin from the nucleolus to the perinuclear region was proposed to enhance viral mRNA translation. 74 The association of nucleolin with the 5' UTR IRES of rhinovirus and poliovirus stimulated the translation of viral proteins in vitro and in vivo.…”
Section: Nucleolin Target Transcriptsmentioning
confidence: 99%
“…NCL is involved in attachment or entry of several unrelated viruses, including human parainfluenza virus type 3, respiratory syncytial virus, Crimean-Congo hemorrhagic fever virus, Japanese encephalitis virus (JEV), and HIV (41)(42)(43)(44)(45)(46)(47). NCL colocalizes with hepatitis D virus delta antigen and interacts with herpes simplex virus 1 protein US11, cytomegalovirus UL44, white-spot syndrome virus VP15, influenza virus (H3N2) NS1, and the NS5B protein of hepatitis C virus.…”
mentioning
confidence: 99%